(3JdNjU GdeSJOQc ddMGces - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GdMGce GdfjSGHhQj , eMeO Hf YHO Gddg Hf MeOhjg Hf fYje GdVHj GdWgeGfj GdfjSGHhQj, CHh YHO Gddg, GdMGce, GHf GdHjY,J (B405 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe YdjfG HGdJhMjO cJGH GdEjeGf GHf YLdGf Yf GdbYbGY Hf Mcje s
(3BNQgG (B:s
(3bGd (B: (3CYLRJ Cf Jchf eKd YLhR Hfi GSQGFjd aPcQ OdGdJgG Ydi YXGe jhSa hbO eQ BNQ GdeLdO GdChd s
(3GdfSNI HgG MhGTs
(3ai ChdgG Jedc ddMGaX GHf MLQ GdYSbdGfi SfI (B802 (3hJedc BNQ dSHWg SfI (B844 (3GdMhGT HNW GHf MLQ HgG fXGe GdJYbjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B238s
Keywords: (3GdMOjK h GdeUWdMs